Barley guanine nucleotide exchange factor HvGEF14 is an activator of the susceptibility factor HvRACB and supports host cell entry by Blumeria graminis f. sp. hordei - Trutzenberg, Adriana; Engelhardt, Stefan; Weiß, Lukas; Hückelhoven, Ralph (Molecular plant pathology, 2022)
In barley (Hordeum vulgare), signalling rat sarcoma homolog (RHO) of plants guanosine triphosphate hydrolases (ROP GTPases) support the penetration success of Blumeria graminis f. sp. hordei but little is known about ROP activation. Guanine nucleotide exchange factors (GEFs) facilitate the exchange of ROP‐bound GDP for GTP and thereby turn ROPs into a signalling‐activated ROP‐GTP state. Plants possess a unique class of GEFs harbouring a plant‐specific ROP nucleotide exchanger domain (PRONE). Here, we performed phylogenetic analyses and annotated barley PRONE‐GEFs. The leaf epidermal‐expressed PRONE‐GEF HvGEF14 undergoes a transcriptional down‐regulation on inoculation with B. graminis f. sp. hordei and directly interacts with the ROP GTPase and susceptibility factor HvRACB in yeast and in planta. Overexpression of activated HvRACB or of HvGEF14 led to the recruitment of ROP downstream interactor HvRIC171 to the cell periphery. HvGEF14 further supported direct interaction of HvRACB with a HvRACB‐GTP‐binding CRIB (Cdc42/Rac Interactive Binding motif) domain‐containing HvRIC171 truncation. Finally, the overexpression of HvGEF14 caused enhanced susceptibility to fungal entry, while HvGEF14 RNAi provoked a trend to more penetration resistance. HvGEF14 might therefore play a role in the activation of HvRACB in barley epidermal cells during fungal penetration. The PRONE‐domain guanine nucleotide exchange factor GEF14 may activate the ROP GTPase RACB for recruitment of downstream factors during fungal invasion into barley. epidermal cells.